1983
DOI: 10.1084/jem.157.5.1448
|View full text |Cite
|
Sign up to set email alerts
|

Expression of passively transferred immunity against an established tumor depends on generation of cytolytic T cells in recipient. Inhibition by suppressor T cells.

Abstract: Recent publications from this laboratory (1, 2) have shown that it is possible to cause the regression of established immunogenic murine tumors by the passive transfer of tumor-sensitized T cells from immunized donors, provided the tumor-bearing recipients have been made T cell-deficient by thymectomy and irradiation. The need for T cell-deficient tumor-bearing recipients to demonstrate successful adoptive immunotherapy suggested the existence in normal tumor bearers ofa T cell-dependent mechanism that prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(49 citation statements)
references
References 28 publications
1
48
0
Order By: Relevance
“…In the early 1980s it was demonstrated that ACT of tumor-sensitized lymphocytes was effective only if the recipient was T-cell-deficient by thymectomy and irradiation. 26 In another model, CD8 + T cells isolated from tumor-draining lymph nodes of mice bearing MCA 205 sarcoma actively proliferated and rejected the pulmonary metastases after total body irradiation (TBI). 27 We have explored the role of lymphodepletion using a transgenic mouse model expressing the pmel-1 T-cell receptor (TCR), which is specific for the murine gp100 melanoma-associated antigen.…”
Section: Rationale For Immunodepletionmentioning
confidence: 99%
“…In the early 1980s it was demonstrated that ACT of tumor-sensitized lymphocytes was effective only if the recipient was T-cell-deficient by thymectomy and irradiation. 26 In another model, CD8 + T cells isolated from tumor-draining lymph nodes of mice bearing MCA 205 sarcoma actively proliferated and rejected the pulmonary metastases after total body irradiation (TBI). 27 We have explored the role of lymphodepletion using a transgenic mouse model expressing the pmel-1 T-cell receptor (TCR), which is specific for the murine gp100 melanoma-associated antigen.…”
Section: Rationale For Immunodepletionmentioning
confidence: 99%
“…T cells were first shown to suppress immune responses in the 1970s (9,10). Although some work continued through the 1980s (11,12), the failure to identify antigen-specific factors and unique identifying molecules that caused immune suppression led to stagnation of this field. Interest was rekindled in the mid-1990s when Sakaguchi et al (13) showed that a small population of CD4 + T cells that coexpressed the IL-2 receptor a-chain (CD25) could control autoreactive CD4 + T cells in vivo.…”
Section: Foxp3mentioning
confidence: 99%
“…Tumor-specific Th cells, though not directly tumoricidal, may play an important role in tumor rejection through the release of lymphokines that activate other effector cells (9,34), and we have shown such cooperation between Th cells and CTL (Fig.6). Lake and Mitchison (35) predicted some time ago that Th cells and CTL could cooperate by "associative recognition" of antigens expressed independently, and our findings are consistent with this hypothesis .…”
Section: Resultsmentioning
confidence: 99%